Determinants of Behavioral Intention Toward Telemedicine Services in Indonesia Post-Pandemic COVID-19 - Desi S.W. Utami; Fajri Satria Wika; Hertinur Betthy S., Oscar; Oscar Oscar (Syntax Idea)
The COVID-19 pandemic has significantly disrupted daily life & accelerated the adoption of digital technologies across various sectors, including healthcare. In Indonesia, this shift has prompted the rapid development and implementation of Telemedicine services by both start-ups and established healthcare institutions. This study aims to identify the factors that influence customer intention to use Telemedicine services in the post-pandemic period, using the Unified Theory of Acceptance and Use of Technology (UTAUT2) model. The research focuses on five key variables: Price Value, Effort Expectancy, Geographical Location, Performance Expectancy, and Social Influence. Data collected from 507 respondents across Indonesia through an online questionnaire reveals that user satisfaction is critical for further use of Telemedicine services. The findings indicate that improvements in the affordability, user-friendliness, accessibility, effectiveness, and social endorsement of Telemedicine services significantly enhance user satisfaction. The study provides practical recommendations for Telemedicine providers to improve these factors, thereby increasing customer retention and adoption rates. This research contributes to the understanding and offers insights for optimizing Telemedicine services in Indonesia in the evolving post-pandemic behaviors